A wind of change - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Information for Agricultural and Rural Development in ACP Countries: New Stakeholders, New Media and Priority Themes, Synthesis on the CTA Seminar, Paris, June 2000. CTA, 2001. 28 pp. ISBN 92 9081 2494 CTA number 1050, 5 credit points